2002
DOI: 10.1007/s002340100636
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging of metastatic disease to the brain with gadobenate dimeglumine

Abstract: Seventy-four patients with one to eight proven intraaxial brain metastases received a total cumulative dose of 0.2 mmol/kg bodyweight gadobenate dimeglumine, administered as sequential injections of 0.05, 0.05 and 0.1 m mol/kg over a 20-min period. MR imaging was performed before the first administration (T2- and T1-weighted sequences) and after each injection of contrast agent (T1-weighted sequences only). Quantitative assessment of images revealed significant (P <0.01) dose-related increases in lesion-to-bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
12
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 18 publications
4
12
0
Order By: Relevance
“…In other words, a mean increase in quantitative lesion enhancement of approximately 30% was noted between a dose of 0.1 mmol/kg and a dose of 0.2 mmol/kg of gadoteridol. Similar findings have been noted previously in studies that involved a comparison of cumulative doses of gadobenate for the detection of cerebral metastases (56,57). In our study, similar mean increments of approximately 30% for gadobenate compared with gadopentetate were noted by all three blinded readers for both lesion-to-brain or lesion-to-spine CNR and percentage of lesion enhancement.…”
Section: Determinations Of Lesion-to-brain or Lesion-to-spine Cnr Accsupporting
confidence: 83%
“…In other words, a mean increase in quantitative lesion enhancement of approximately 30% was noted between a dose of 0.1 mmol/kg and a dose of 0.2 mmol/kg of gadoteridol. Similar findings have been noted previously in studies that involved a comparison of cumulative doses of gadobenate for the detection of cerebral metastases (56,57). In our study, similar mean increments of approximately 30% for gadobenate compared with gadopentetate were noted by all three blinded readers for both lesion-to-brain or lesion-to-spine CNR and percentage of lesion enhancement.…”
Section: Determinations Of Lesion-to-brain or Lesion-to-spine Cnr Accsupporting
confidence: 83%
“…Early dosing studies demonstrated that, as expected, double doses of gadobenate dimeglumine (MultiHance®) are potentially beneficial with increased sensitivity in brain lesion detection, but, unlike other contrast agents, no further benefit is derived from triple doses [15,19]. However, the more significant evidence of improved diagnostic performance with the higher relaxivity agent derives from a series of intraindividual crossover studies directly comparing gadobenate dimeglumine (MultiHance®) with gadopentetate dimeglumine (Magnevist®, Bayer Schering Pharma AG, Berlin, Germany) [20][21][22][23][24][25], gadoterate meglumine (Dotarem®, Guerbet Aulnay s/ Bois, France) [20,22], gadodiamide (Omniscan™, GE Healthcare AS, Oslo, Norway) [20,26] and gadofosveset trisodium (Vasovist®) [6].…”
Section: Applications Of Contrast-enhanced Mri In Neuroimagingmentioning
confidence: 99%
“…Dosage of MRI contrast can impact detection of metastatic disease. Studies have shown increasing detection of metastases with increasing doses of MRI contrast and increased detection of brain metastases with double or triple contrast doses compared to single contrast dose MRIs [10,[21][22][23][24]. More recent studies have demonstrated a significant improvement in effects of T1 shortening and lesion detection even using half the dose of contrast agent if the examination if performed using higher field strength magnet of 3 Tesla compared to 1.5 Tesla [25].…”
Section: Neuroimaging Techniquesmentioning
confidence: 97%